Identifying barriers that prevent US insured adults at-risk for and diagnosed with type 2 diabetes from accessing primary care services: An exploratory study - Tamara Crawford (Journal of Health and Social Sciences)
Introduction: Type 2 diabetes is a condition that affects millions of individuals within the United States and it is one of the leading causes of death. Access to quality care is necessary to decrease the risk of developing type 2 diabetes and associated complications. This study focused on assessing the barriers that prevented insured individuals, identified through a community health screening as at-risk for or suffering from type 2 diabetes, from accessing primary care services. Methods: A quali-quantitative design was used in this study. Participants were recruited through convenience sampling and 64 participants were identified through community outreach events sponsored by the Florida Atlantic University’s (FAU) Community Health Center. Barriers were measured through the ‘Barriers to Care’ Survey Instrument, which was administered face-to-face at community outreach events. Results: Descriptive analyses indicated that participants identified cost of care as the most reported barrier (73.4% of sample) to accessing care. Lack of family and friend support was the least reported barrier (7.8% of sample). Regression analyses showed a significant association between reported barriers and participants’ access to primary care services by measuring participants’ last primary doctor’s appointment (R2 = 0.47, P = 0.001). Three factors significant resulted in predicting participants’ last primary doctor’s appointment: ‘not having time to go to the doctor’ (P = 0.022), ‘feeling too sad about disease to see a doctor’ (P = 0.021), and ‘not feeling sick’ (P = 0.001). Discussion and Conclusions: Findings have important clinical implications since addressing identified barriers can lead to increased access to primary care services and enhanced health outcomes. Future research should focus on the significant impact of self-management techniques, sociocultural factors, and psychosocial factors to help inform researchers how they impact the barriers associated with individuals at-risk for or suffering from type 2 diabetes. Having health insurance is not the only answer to accessing primary care.